Nonlinear dynamics of full-range CNNs with time-varying delays and variable coefficients - Liu, Shuxin; Jiang, Haijun; Zhang, Liwei; Mei, Xuehui (Nonlinear Analysis: Modelling and Control, 2020)
In the article, the dynamical behaviours of the full-range cellular neural networks (FRCNNs) with variable coefficients and time-varying delays are considered. Firstly, the improved model of the FRCNNs is proposed, and the existence and uniqueness of the solution are studied by means of differential inclusions and set-valued analysis. Secondly, by using the Hardy inequality, the matrix analysis, and the Lyapunov functional method, we get some criteria for achieving the globally exponential stability (GES). Finally, some examples are provided to verify the correctness of the theoretical results.
Keywords: cellular neural networks; globally exponential stability; differential inclusions; time-varying delays